ANALISIS FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2014 - Mayang Murni (Jurnal Investasi Islam, 2017)
The objective of the research was to examine the influence of firm size, firm age, CR, DER, ROA, ROE, NPM, EPS, and PER on stock price. The population was manufacture companies listed in BEI (the Indonesia Stock Exchange) in the period of 2010-2014. The samples were 73 manufacture companies listed in BEI, taken by using purposive sampling technique so that there were 365 observations. The data were secondary data which were obtained from financial statement and were analyzed by using multiple linear regression analysis with an SPSS 21 software program. The result of the research showed that firm size, firm age, Current Ratio, and PER had positive and significant influence on stock price. NPM and ROA had positive impact but insignificant influence on stock price. DER, ROE, and EPS had negative and insignificant influence on stock price.